2013
DOI: 10.7314/apjcp.2013.14.5.3131
|View full text |Cite
|
Sign up to set email alerts
|

Role of Print and Audiovisual Media in Cervical Cancer Prevention in Bangladesh

Abstract: Background: Visual inspection of cervix with acetic acid (VIA) is offered at 252 centers in 64 districts of Bangladesh. VIA+ve women are managed at colposcopy clinics of Bangabandhu Sheikh Mujib Medical University (BSMMU) and 14 Medical College Hospitals (MCHs). This research work has been supported by 'UICC Cancer Prevention Campaign' programme. Objectives: This study explored the role of print materials and electronic media to improve cervical cancer screening in the present socio-cultural context of Banglad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 11 publications
3
12
0
Order By: Relevance
“…Other barriers were lethargic attitude (44.87%), economic barrier (time and money), availability, fear and hesitation. Nessa et al showed that more emphasis must be given to use of print and audiovisual media in cervical and breast cancer prevention (Nessa et al, 2013). Tan et al (2010) showed that mass media and education were the most common sources of information of cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Other barriers were lethargic attitude (44.87%), economic barrier (time and money), availability, fear and hesitation. Nessa et al showed that more emphasis must be given to use of print and audiovisual media in cervical and breast cancer prevention (Nessa et al, 2013). Tan et al (2010) showed that mass media and education were the most common sources of information of cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Under certain circumstances, the media can contribute to amplifying the community agenda for social changes (Demers and Viswanath, 1999;Nessa et al, 2013;Saleh et al, 2012). Organized efforts for the promotion of public health, such as population-based health communication campaigns, often use the mass media as a powerful tool (Beaudoin et al, 2006).…”
Section: Media Advocacymentioning
confidence: 99%
“…This is now available at 252 facilities, from tertiary to primary care levels [4]. The screening uptake among women aged 30-59 years has been low (8.6%), resulting in low coverage of the target population [5]. Furthermore, poor compliancewithcolposcopy, whenindicated, has beenreported [4,5].…”
Section: Introductionmentioning
confidence: 99%